Retracted: Analisis Hope pada Atlet Bulu Tangkis Indonesia Juara Dunia Era ’70 dan ’90 - Esther Widhi Andangsari; Pingkan C.B. Rumondor (Bina Nusantara University, 2013)
RETRACTED At the request of the Authors, Journal Editor and the Publisher, the following article has been retracted. Andangsari, E. W. & Rumondor P. C. B. (2013). Analisis Hope pada Atlet Bulu Tangkis Indonesia Juara Dunia Era ’70 dan ’90. Humaniora 4(1), 500-507, DOI: 10.21512/humaniora.v4i1.3458. Following investigation into this article, it has been determined that the article has been published previously in another journal by the same author; Andangsari, E. W. & Rumondor P. C. B. (2012). Analisis Hope pada Atlet Bulu Tangkis Indonesia Juara Dunia Era ’70 dan ’90. Jurnal Psikologi Ulayat 1(1), 25-36, DOI: 10.24854/jpu12012-8. The document and its content have been removed from Humaniora, and reasonable effort should be made to remove all references to this article.